SOSIALISASI DAN PERSEPSI BANK SYARIAH (KAJIAN KEBIJAKAN ENKULTURASI NILAI-NILAI BANK SYARIAH DALAM MASYARAKAT) - Sadhana, Kridawati (Jurnal Keuangan dan Perbankan, 2012)
The name of someone, something, institution had a certain meaning. A meaning depended so much on someonesperception to an object. Perception of society to Sharia Bank had an impact to society behavior toward ShariaBank. There was a gap here between bank and society which had to be acted as a bridge through policy andsocialization program. Socialization policy which was planned, adaptive, and interesting could minimize themisperception risk. Socially, sosialization program was the enculturization of sharia bank values process, andit was understood as the form of civil education.